Effects of modified tall oil and vitamin e on growth performance and carcass characteristics of growing-finishing barrows - O'Quinn, P.R.; Waylan, A.T.; Woodworth, J.C.; Koo, S.I.; Nelssen, Jim L.; Unruh, John A.; Goodband, Robert D.; Tokach, Michael D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A trial was conducted to investigate the interactive effects of modified tall oil (MTO) and vitamin E on growth performance and carcass characteristics of growing-finishing barrows. Feeding MTO resulted in increased ADG and improved F/G during the growing phase; otherwise dietary treatment did not affect growth performance during the rest of the trial or overall. Feeding MTO also decreased backfat thickness and increased belly firmness. Increasing vitamin E in diets containing MTO decreased drip loss percentage of the loin. These results indicate that MTO may function as a growth promoter; reduce backfat; and in conjunction with vitamin E, itnprove some aspects of meat quality.
Keywords: Swine; Modified tall oil; Vitamin E; Growth performance; Carcass characteristics